Effect of some process variables on nickel electroplating of low carbon steel (2015)
"This research work investigated the effect of current density, bath concentration, bath solution volume and electroplating time on nickel electroplating of low carbon steel. Varying voltage between 0.3 and 0.8 V, bath concentration between 0.27 g/cm3 (0.79 mol/dm3) and 0.35 g/cm3 (1.02 mol/dm3), electroplating time between 10 and 30 minutes and bath solution volume between 200 and 700 cm3, the effect of these process variables on electroplating was studied. The temperature was kept in conformity with Watt’s method at 50 ±5°C. It was observed that a bath concentration of 0.31 g/cm3 (0.89 Mol/ dm3) concentration gave the best nickel deposit at 0.5V for 15 minutes. This would correspond to a Watt solution of composition: nickel sulphate-230 g/l, nickel chloride- 46.5 g/l and boric acid-30.8 g/l with a pH of 4.18. Higher Watt bath concentration did not yield good results as plating thickness decreased and there was no luster. It was also observed that increasing time of plating served to increase plating thickness and did not affect brightness of plating. However non-uniform nickel deposition was observed for longer plating time. Increase in voltage served to increase rate of electrodeposition with the exceptions of 0.7 V where a long streak of plating was observed on substrate instead of uniform plating and 0.8V where plating lacked brightness having a burnt appearance. Bath volumes of between 200-500 cm3 were observed to be best for the coupons used (15mm × 20mm). Bath volumes above 500cm3 gave black plating appearance. "